2014
DOI: 10.1002/etc.2469
|View full text |Cite
|
Sign up to set email alerts
|

Use of an avian hepatocyte assay and the avian toxchip polymerse chain reaction array for testing prioritization of 16 organic flame retardants

Abstract: Risk assessors are challenged with the task of providing data for an increasing number of priority chemicals. High-throughput toxicity screening methods--which permit rapid determination of toxic, molecular, and/or biochemical effects of a wide range of chemicals--are essential to help meet this demand. The avian embryonic hepatocyte in vitro screening method has been utilized in the authors' laboratory to assess the effects of a wide range of environmental contaminants on cytotoxicity and mRNA expression of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
120
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(126 citation statements)
references
References 49 publications
(78 reference statements)
4
120
1
Order By: Relevance
“…Our results fit this general pattern. Of all the findings here, the possible reduced survival rate at lower levels (100 ng/g) than observed for other OPFRs seem to support suggestions that TDCIPP might be a priority for further study among OPFRs just as Porter et al (2014) recommended from their in vitro work.…”
Section: Accepted Manuscriptsupporting
confidence: 69%
See 1 more Smart Citation
“…Our results fit this general pattern. Of all the findings here, the possible reduced survival rate at lower levels (100 ng/g) than observed for other OPFRs seem to support suggestions that TDCIPP might be a priority for further study among OPFRs just as Porter et al (2014) recommended from their in vitro work.…”
Section: Accepted Manuscriptsupporting
confidence: 69%
“…This study builds upon previous in vitro studies involving embryonic and adult birds showing that toxic responses in avian models can vary among OPFRs. For example,Porter et al (2014) used hepatocyte cultures from chickens and herring gulls to show that changes in gene expression and cytotoxicity can vary following exposure to 16 flame retardant chemicals. Notably TDCIPP and TMPP were among the most active in eliciting in vitro responses, though effects may differ between the liver and the brain.While the present study (that includes both structural and functional measures across multiple levels of biological organization) contributes new knowledge about the potential neurodevelopmental effects of relevant OPFRs towards birds, some limitations of the current study warrant mention.…”
mentioning
confidence: 99%
“…Several BFRs along with their metabolites have been shown to disrupt endocrine and reproductive systems (Khalaf et al, 2009;Legler and Brouwer, 2003;Porter et al, 2013;Wang et al, 2013) acting as either agonist or antagonist to different hormone receptors. A number of hydroxylated and methoxylated polybrominated diphenyl ethers (HO-/MeO-PBDEs) have recently been shown to possess antiandrogenic properties (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Toxicological studies have shown that OPFRs have the potential to cause adverse reproductive, endocrine and systemic effects in animals as a result of long term exposure to animals (Dishaw et al, 2011;Liu et al, 2012;Porter et al, 2014;Van der Veen and de Boer, 2012). Aryl-OPFRs have been shown to contribute to heart toxicity by disturbing the expression of transcriptional regulators in zebrafish (Du et al, 2015).…”
Section: Introductionmentioning
confidence: 99%